Carotid revascularization and medical management for asymptomatic carotid stenosis – Hemodynamics (CREST-H): Study design and rationale. Issue 9 (December 2018) - Marshall, Randolph S; Lazar, Ronald M; Liebeskind, David S; Connolly, E Sander; Howard, George; Lal, Brajesh K; Huston, John; Meschia, James F; Brott, Thomas G
Rationale: For patients with asymptomatic high-grade carotid stenosis, clinical investigations have focused on preventing cerebral infarction, yet stenosis that reduces cerebral blood flow may independently impair cognition. Whether revascularization of a hemodynamically significant carotid stenosis can alter the course of cognitive decline has never been investigated in the context of a randomized clinical trial. Hypothesis: Among patients randomized in the Carotid Revascularization and Medical Management for Asymptomatic Carotid Stenosis (CREST-2) trials, the magnitude of treatment differences (revascularization versus medical management alone) with regard to cognition will differ between those with flow impairment compared to those without flow impairment. Sample size: We will enroll approximately 500 patients from CREST-2, of which we anticipate 100 will have hemodynamic impairment. We estimate 93% power to detect a clinically meaningful treatment difference of 0.5 SD. Methods and design: We will use perfusion-weighted magnetic resonance imaging to stratify by hemodynamic status. Linear regression will compare treatment differences, controlling for baseline cognitive status, age, depression, prior cerebral infarcts, silent infarction, white matter hyperintensity volume, and cerebral microbleeds. Study outcomes: The primary outcome is change in cognition at one year. Secondary outcomes include silent infarction, change in white matter hyperintensity volume, number of cerebral microbleeds, and cortical thickness over one year. Discussion: If cognitive impairment can be shown to be reversible by revascularization, then we can redefine "symptomatic carotid stenosis" to include cognitive impairment and identify a new population of patients likely to benefit from revascularization. Trial Registration: US National Institutes of Health (NIH) clinicaltrials.gov NCT03121209